Hak asuh anak diluar nikah perspektif kesetaraan gender - Natasya, Alvionita Nefa (Maliki Interdisciplinary Journal, 2024)
Indonesia only has a family relationship with his mother. It can also affect other rights such as custody and inheritance rights of children out of wedlock who only have a relationship with their mother. However, after the Constitutional Court's decision appeared, it stated that a child out of wedlock had a parenting and civil relationship with his mother and a relationship with his father as evidenced by technology or through a DNA test. So that in these provisions experience differences. Therefore, with these differences, the custody of children outside of marriage will be studied from the perspective of gender equality. Qualitative descriptive is a type of research that is used so that it requires in-depth analysis. While the data collection uses library research, namely by reading, studying and understanding the literature of books, articles and journals so that data is obtained consistently and systematically. The results of his research are that if the custody of children outside of marriage is viewed from gender equality, then the provisions described above contain an element of injustice.